Seroprevalence of RSV IgG Antibodies Across Age Groups in Poland After the COVID-19 Pandemic: Data from the 2023/2024 Epidemic Season - Barbara Poniedziałek; Wiktoria Majewska; Katarzyna Kondratiuk; Aleksander Masny; Anna Poznańska; Karol Szymański; Katarzyna Łuniewska; Emilia Czajkowska; Bartosz Mańkowski; Lidia B. Brydak; Krzysztof Tomasiewicz; Robert Flisiak; et al. (Vaccines, 2025)
Background/Objectives: Respiratory syncytial virus (RSV) is a leading cause of respiratory infections across all age groups, with the greatest burden observed in young children and older adults. The COVID-19 pandemic significantly disrupted RSV circulation, resulting in an immunity gap and altered transmission dynamics. This study aimed to assess the seroprevalence of anti-RSV IgG antibodies in the Polish population during the 2023/2024 epidemic season. To our knowledge, this is the first study to characterize RSV seroprevalence at the population level in Poland. Methods: A total of 700 serum samples from individuals across different age groups were analyzed using a commercial assay to detect anti-RSV IgG antibodies. Seroprevalence and antibody levels, expressed as the index of positivity (IP), were examined by age and sex. Results: The overall seroprevalence of anti-RSV IgG antibodies was 91.4%. Antibody positivity increased markedly from 35.5% in infants aged 0–1 years to over 90% in children aged 4–5 years, reaching nearly universal levels in older age groups, including 99.1% in adults aged ≥60 years. Median IP values also rose with age, peaking in individuals aged ≥60 years. No significant differences in seroprevalence were observed between sexes, though older men showed slightly higher median IP values, potentially reflecting greater cumulative RSV exposure. Conclusions: This study provides key insights into the post-pandemic landscape of RSV immunity in Poland. The high seroprevalence across most age groups underscores widespread prior exposure, while the lower rates in infants highlight a continued vulnerability. These findings support the development and implementation of targeted immunization strategies, particularly for infants and older adults.